Occupational exposure to manganese and risk of creatine kinase and creatine kinase‐MB elevation among ferromanganese refinery workers. Issue 5 (29th February 2020) - Huang, Sifang; Liu, Zhenfang; Ge, Xiaoting; Luo, Xiaoyu; Zhou, Yanting; Li, Defu; Li, Longman; Chen, Xiang; Huang, Lulu; Cheng, Hong; Hou, Qingzhi; Zan, Gaohui; et al.
Abstract: Background: Elevated exposure to manganese (Mn) could induce cardiovascular dysfunction. However, limited research is available on the effects of occupational Mn exposure on myocardial enzymes. We aimed to evaluate the relationships between Mn exposure and myocardial enzyme elevation among Mn‐exposed workers. Methods: Data were from a follow‐up investigation of a Mn‐exposed workers healthy cohort in 2017. A total of 744 workers were divided into low‐exposure and high‐exposure groups according to Mn time‐weighted average (Mn‐TWA) of less than or equal to 0.15 mg/m 3 or greater than 0.15 mg/m 3, respectively. Serum levels of myocardial enzymes, including creatine kinase (CK) and creatine kinase‐MB (CK‐MB), lactic dehydrogenase, α‐hydroxybutyrate dehydrogenase, and aspartate transaminase, were assessed, as well as airborne Mn exposure levels. Results: After adjustment for sex, body mass index, seniority, education, current smoking status, current drinking status, and hypertension, Mn‐TWA levels were positively associated with the risk of CK elevation (odds ratio [OR] = 1.47 (95% confidence interval [CI]: 1.18‐1.83) per interquartile range [IQR] increase), and risk of CK‐MB elevation [OR = 1.57 (95% CI: 1.03‐2.38) per IQR increase]. In a stratified analysis, Mn‐TWA levels were positively correlated with CK elevation in workers of seniority greater than 19 years, male workers, current smokers, and drinkers. Conclusion: Our results suggest that occupational exposure to Mn is associated with increased risk of CK and CK‐MB elevation. The potential mechanisms of the associations between airborne exposure to Mn and increased risk of these myocardial enzyme elevations warrant further investigation.